Contingent prenatal screening for frequent aneuploidies with cell-free fetal DNA analysis - M. Rosario Torres Aguilar; Pilar Carrasco Salas; Cristina Santos Rosa; Guadalupe Bueno Rodríguez; Eduardo Martínez-Bonet; Práxedes Carreto Alba; Antonio León-Justel; M. Reyes Granell Escobar (Elsevier, 2021)
Objective: To analyze the results of contingent screening for common aneuploidies at our center from June 2017 to June 2019. Materials and methods: Traditional screening tests were performed using a combination of biochemical markers and ultrasound measurements in the first and second trimesters to assess the risk of trisomies 21 (T21), 18 (T18) and 13 (T13). Cell-free DNA (cf-DNA) testing was offered (Harmony test) to pregnant women at high risk (>1/280 for T21 and > 1/150 for T13 and T18) and a normal early morphology scan. In positive cases, prenatal sampling was strongly recommended to confirm the results by gold standard methods (QF-PCR and karyotyping). Newborns' phenotypes were corroborated after birth in all cases. Results: In this prospective study, 8153 pregnant women were enrolled, resulting in 390 at high risk according to traditional screening tests. cfDNA testing was offered to 383 women. Traditional screening tests showed a false negative rate of 9.68% for T21. Traditional test sensitivity for T21 was 90.3%, for a false positive rate of 4.17% and a positive predictive value of 7.6%. The positive and negative predictive value for cfDNA testing was 100%. The approach used avoided invasive procedures in 91.3% of women at high risk. The prevalence of chromosomal abnormalities in the population analyzed was 1 in 164, and 1 in 210 for T21. Conclusions: Our results show that offering cf-DNA testing to women at high risk in traditional tests (including those with risks >1 in 50) significantly reduces false positives and, therefore, the number of invasive tests. Extending the use of cf-DNA testing to intermediate risk categories may be cost effective.